Natural rubber foams with anisotropic cellular structures: Mechanical properties and modeling - Oliveira-Salmazo, Leandra [UNESP]; Lopez-Gil, Alberto; Silva-Bellucci, Felipe; Job, Aldo E. [UNESP]; Rodriguez-Perez, Miguel A. (Elsevier, 2016)
Natural rubber foams are biobased and lightweight products which have found their main field of application in comfort products such as mattresses and pillows. They are generally produced from chemical foaming processes in which the expansion of the polymer is isotropic and hence, their properties are not directionally dependent. However, this dependency could be interesting for certain structural and thermal insulating applications. In this work, elastomeric foams based on natural rubber with a medium relative density (around 0.3) and with varied cellular structures in terms of the shape anisotropy ratio of the cells were produced by a chemical foaming process in which expansion was restricted to only one direction inside a mold. The use of solid precursors of different dimensions, the elastomeric properties of natural rubber and the crosslinking by sulfur of the polymer matrix during foaming allowed foams to be obtained with anisotropy ratios between 0.90 and 2.48 at the same density and with the same properties as the polymeric matrix. In this particular case the study was focused on analysing their compressive modulus and its relationship with the anisotropy of the cellular structure by employing analytical models generally used to describe the mechanical behavior of anisotropic foams.
Keywords: Anisotropy; Biopolymer; Cross-linked; Foams; Natural rubber